PENGARUH SISTEM PENYIMPANAN DAN PEMELIHARAAN TERHADAP KESIAPAN RUDAL C 802 DI ARSENAL - Ahmad Susilo Nurhuda; Edy Iwan Bangun; Rama Rimeiar Putra (Faculty of Science and Technology University of Pramita Indonesia, 2023)
The Navy as the national defense force at sea has the task of carrying out the duties of the TNI in the field of defense must be supported by ship elements which are the main tool that is ready to fight at any time equipped with guided missiles (missiles). One of the missiles installed on the KRI is the C 802 missile which is made in China. Arsenal as a work unit that has the main task of carrying out the maintenance and storage of special weapons. In carrying out the storage and maintenance of the C 802 missile at the Arsenal, there are problems that affect the readiness of the C 802 missile, including problems with the condition of the container launcher, calibration of the instrument test bench and implementation of preventive maintenance. The purpose of this study was to analyze the effect of the condition of the container launcher, instrument test bench calibration and implementation of preventive maintenance on the readiness of the C 802 missile. This study used a quantitative method with data collection carried out by distributing questionnaires. The sample used in this study is Arsenal personnel who are responsible for carrying out the storage and maintenance of special weapons, totaling 60 people using the saturated sampling method. The result data from the questionnaire were tested using SPSS 26 for Windows software. The results showed that the condition of the container launcher, calibration of the instrument test bench and the implementation of preventive maintenance had a significant effect both partially and simultaneously, had a positive and very strong relationship simultaneously of 0.924 and contributed 85.3% to the readiness of the C 802 missile.